How is human trafficking regulated in the UK?: a critical examination of the UK's anti-trafficking response - Gaitis, Konstantinos Kosmas (Law thesis and dissertation collection, 2021)
Over the last decade, jurisdictions across the UK have paid increased attention to the problem of human trafficking, as exemplified by the enactment of new specialised legislation (reserved and devolved), the increase in criminal justice and border control efforts, as well as the adoption of the UK-wide National Referral Mechanism (‘NRM’), based on the system designed by the Organisation for Security and Co-operation in Europe (‘OSCE’), to identify and deal with potential victims of human trafficking, perpetrators and their respective cases. This Mechanism, along with the UK’s wider approach to human trafficking, have been criticised by NGOs and scholars for various reasons, such as poor identification skills of those officials who first come into contact with victims (known as first responders), lack of sufficient support and benefits to victims, as well as inequalities in decision outcomes between UK/EU and non-UK/EU victims, leading to governmental reviews and planned reforms. Despite efforts to understand and tackle the issues of the NRM by NGOs, researchers and policy makers, there has been limited attention paid by commentators to the policy context in which the NRM has been implemented and what this might reveal about the aforementioned problems of the Mechanism. In addition, efforts to examine human trafficking, arguably, have failed to fully capture all its angles and in particular to understand its tripartite nature: the victims’ rights/needs aspect of it, the traffickers’ side, as well as the state side (origin, destination and transit states) and particularly how a destination state regulates trafficking in relation to broader overarching issues affecting trafficking, meaning mainly immigration. Through documentary analysis of the main policies on human trafficking issued by the UK government at Westminster and the devolved governments, which constitute the NRM’s foundations and context, a series of qualitative interviews with professionals involved in UK’s anti-trafficking efforts and a case study of a female domestic survivor trafficked for sexual exploitation, this thesis offers a critical examination of how the UK regulates human trafficking, focusing on adult trafficking victims. Building on a theoretical framework, which draws on Christie’s notion of ideal victims and offenders and Sharapov’s examination of the images of trafficking victims and perpetrators in early-2010s UK policies, the thesis highlights how the dominant narrative of UK policies still tends to revolve around the idealisation of trafficking victims and demonisation of traffickers, often not paying respect to the full spectrum of human trafficking as underlined by literature, while promoting unrealistic goals, such as total trafficking elimination, primarily aiming to the UK’s heroification as a leading anti-slavery force. Still, a slowly growing tendency to start focusing on a wider range of trafficking cases, on the range of victims based on varying levels of consent or trafficking experiences, the range of traffickers based on varying levels of organisation and the frequent fluidity between victims-traffickers was identified mainly in Westminster policies and much less in policies issued by the devolved governments. Simultaneously, the thesis pinpoints a polarisation between interviewees depending on their professional background, meaning between NGO interviewees and law enforcement interviewees. The former tended to idealise victims more and recognise the existence of a spectrum for traffickers and the latter underlined the spectrum for victims between those who consented to exploitation and those who were deceived/forced, whilst presenting traffickers as almost exclusively organised criminals. NGO interviewees also appeared to be more critical towards the NRM compared to law enforcement participants. Further, the idiosyncrasies of the UK constitutional setting and the deep-rooted ideological differences between Westminster and the Scottish Government have contributed to a fragmented approach across the UK. The different approach of the Scottish Government compared to Westminster renders the prospect of a devolved Scottish NRM worthy of further examination. The structure of the UK as a state that is neither federal nor unitary feeds and will continue to feed on the shortcomings of the UK’s approach to trafficking, with the prospect of the UK regulatory practices radically improving, being thus quite limited. This thesis concludes by confirming and enriching existing literature, which has long pinpointed the existence of a spectrum of trafficking cases, also revealing how the UK’s NRM impacts negatively on domestic victims. Finally, combining left realism in criminology, International Relations currents of thought (realism-idealism) and the theory of conflict of rights, this thesis also tries to enrich the teachings of the contemporary Criminology on immigration, trafficking and asylum, which often restricts itself to heavily moralising judgments on destination state practices. Through the theoretical framework of Criminological Moral Realism, this thesis tries to take into consideration all the crucial angles of such phenomena, as well as the regulatory challenges faced particularly by the destination state, as it seeks to balance between internationally legislated minimum standards of humanitarianist protection, on one hand, and the conflicted duties states have to satisfy (e.g. budget restraints, criminal justice successes) on the other, with the goal to fuse criminological thinking with a strong sense of realism to promote applicable policy improvements.